Pengaruh Price Discount dan Atribut Produk terhadap Minat Beli Ulang Dimediasi oleh Kepuasan Pelanggan pada E-Commerce Lazada: Studi Mahasiswi di Universitas Semarang - Vania Dahayu Cahyarani; Robertus Basiya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In this research the author uses a quantitative research approach. What is meant by quantitative research will emphasize the quality of the data or the depth of the data obtained. The data that will be used in this research data is primary data. The population of this research is all customers who shop at Lazada Semarang e-commerce. Lazada provides a guaranteed product return application service to help consumers if there are problems, the products offered meet consumer needs and desires. Lazada provides a guaranteed product return application service, helps consumers if there are problems, the products offered meet consumer needs and desires, and the admin responds quickly. and features displayed such as product information. So that with the many services provided, consumers will have their own satisfaction.